Is job control under threat in the human services? Evidence from frontline practitioners in Australia, 2003–2012. (June 2015) - Cortis, Natasha; Eastman, Christine
This article examines a component of job quality which is particularly important for human service workers: the level of control they have over their work. Having control over work goals and tasks enables frontline workers to respond appropriately to the needs of the people they serve, so contributes to service quality and client outcomes, as well as employee wellbeing. However, much research has contended that job control is under threat in human service contexts, largely as a result of new public management. We examine these claims and contribute new data showing that levels of job control in the human service workforce have indeed been under pressure in recent years. From 2003 to 2012, Australia's human service workforce did not experience the increase in job control experienced by other workers. In the education industry, levels of job control fell significantly. We discuss these trends in the context of debates about the impact of new public management on frontline human service work and challenges of securing the future provision of good quality services.